2023
DOI: 10.12998/wjcc.v11.i2.268
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic stem cell transplantation in the treatment of acute myeloid leukemia: An overview of obstacles and opportunities

Abstract: As an important treatment for acute myeloid leukemia, allogeneic hematopoietic stem cell transplantation (allo-HSCT) plays an important role in reducing relapse and improving long-term survival. With rapid advancements in basic research in molecular biology and immunology and with deepening understanding of the biological characteristics of hematopoietic stem cells, allo-HSCT has been widely applied in clinical practice. During allo-HSCT, preconditioning, the donor, and the source of stem cells can be tailored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 209 publications
0
4
0
Order By: Relevance
“…After allo-HSCT, aGVHD is a frequent complexity that can happen, especially in those with AML [17,18]. For prompt diagnosis, a precise prognosis, and efficient therapy of aGVHD, it is crucial to find trustworthy, non-invasive biomarkers that may be used to predict, and evaluate the outcomes in aGVHD following allo-HSCT [1,11,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…After allo-HSCT, aGVHD is a frequent complexity that can happen, especially in those with AML [17,18]. For prompt diagnosis, a precise prognosis, and efficient therapy of aGVHD, it is crucial to find trustworthy, non-invasive biomarkers that may be used to predict, and evaluate the outcomes in aGVHD following allo-HSCT [1,11,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…AML is a group of hematologic malignancies with high heterogeneity which is also extended to their metabolic profiles [ 24 26 ]. It was reported recently that FLT3/ITD induce a significant increase in aerobic glycolysis via AKT-mediated upregulation of mitochondrial hexokinase (HK2), and render AML cells highly dependent on glycolysis [ 25 ].…”
Section: Nox Play a Key Role In Flt3/itd Signalingmentioning
confidence: 99%
“…Among these ligaments, the anterior talo bular ligament (ATFL) is the most frequently injured one. 4 Studies have shown that among all ankle joint ligament injuries, ATFL accounts for as high as 66%. 5,6 The ankle joint typical symptoms are persistent stiffness, swelling as well as pain, which may be accompanied by secondary synovitis, tendinitis and muscle weakness.…”
Section: Introductionmentioning
confidence: 99%